Frequency agile micristrip patch slot antenna - Majid, H. A. (2012)
A frequency agile patch to slot antenna is proposed. The proposed antenna is consisted of a microstrip patch and a slot in the ground plane. Seven switches using RF PIN diode BAR 52-02 positions at the slot to produce seven reconfigurable frequencies at 1.87 GHz, 1.96 GHz, 2.08 GHz, 2.2 GHz, 2.41 GHz, 2.74 GHz and 3.19 GHz. The patch resonates at the highest resonant frequency whereas the slot resonates at the lower resonant frequencies. It was found that, at the highest frequency the radiation pattern is directional while at the lower frequencies, a near omni-directional radiation patterns are obtained. Simulated and measured results are used to demonstrate the performance of the antenna.